Reference values for high attenuation areas on chest CT in a healthy, never‐smoker, multi‐ethnic sample: The MESA study. Issue 8 (17th February 2020) - Easthausen, Imaani; Podolanczuk, Anna; Hoffman, Eric; Kawut, Steven; Oelsner, Elizabeth; Kim, John S.; Raghu, Ganesh; Stukovsky, Karen Hinckley; Redline, Susan; McClelland, Robyn L.; Barr, R Graham; Lederer, David J.
ABSTRACT: Background and objective: Normative values for HAA—a quantitative, CT‐based measure of subclinical ILD—in healthy adults are needed to improve interpretability in clinical and research settings. Methods: HAA was measured on full‐lung CT in 3110 participants in the MESA study. Clinical prediction models were developed using a healthy never‐smoker subset with normal spirometry ( n = 696). RMSE on cross‐validation was used as the primary criterion for model selection. Parametric and non‐parametric methods were considered. z‐Scores were calculated for the entire study sample. Associations between z‐scores and several ILD features were estimated. Results: In the healthy never‐smoker subset, the mean age was 69 years with a range of 54–93 years. The median HAA was 4.3% with a range of 2.7–17.8%. Linear regression had better predictive performance than other methods. The final model included race, height, weight, age and sex. The standard error of the estimate was 1.62 with a cross‐validated RMSE of 1.64 and an adjusted R 2 of 0.139. z‐Scores were associated with several ILD outcomes in adjusted models, including ILA (OR: 1.40 per z‐unit; 95% CI: 1.30, 1.52), exertional dyspnoea (OR: 1.08 per z‐unit; 95% CI: 1.02, 1.15) and FVC (expected increase per z‐unit: −2.49; 95% CI: −2.95, − 2.03). Conclusion: We present a reference equation and z‐scores to define expected values of HAA on full‐lung CT to aid HAA interpretation in middle‐aged and older adults. Abstract : To better understand the natural variation of HAA (a novel quantitative CT‐based measure of subclinical ILD), we developed HAA reference equations and z‐scores to define expected values of HAA with adjustment for key demographic and anthropometric variables, and we demonstrated that HAA z‐scores correlate with several ILD features. See related Editorial